Hypertension and Its Predictors in a Squatter Settlement of Karachi - Hafsa Saeed; Fatima Jehangir; Misbah Mohammad; Aliya Mazhar (ziauddin University, 2024)
Background: Hypertension, the 'silent killer', is the cause of high mortality and is one of the major health problems worldwide. This study aimed to determine the frequency of hypertension and its predictors in a squatter settlement in Karachi. Methods: A cross-sectional study (n=212) was conducted at the Family Medicine Clinic, Karachi. The participants aged 18 to 65 years, from Jan 1st to 30th June 2020 were recruited. Thorough examination (including blood pressure, weight, and height) and interviews of the participants were done regarding lifestyle, cardiovascular risk factors, personal and family history of cardiovascular diseases, or other chronic illnesses. The Chi-square test was used to identify the association of the risk factors with hypertension and a p-value <0.05 was considered statistically significant. Results: The overall burden of hypertension calculated was 63(29.7%). The mean age of participants was 39.3+15.4 years. A very strong association (p<0.01) of hypertension (76.5%) was seen with a history of dyslipidemia compared to non-hypertensives (23.5%). Among diabetics, it was found that 84% were hypertensive and 16% were non-hypertensive with a statistically significant (p =0.00) association. Personal history of ischemic heart disease (77.8%, p-value 0.003), transient ischemic attack (TIA)/stroke (100%, p-value 0.087) and family history of premature coronary artery diseases (88.9%, p-value <0.01) were seen more common in individuals with high blood pressure. Conclusion: The frequency of hypertension is high in a squatter settlement in Karachi and it is highly associated (p<0.01) with the development of dyslipidemia, diabetes, family history of coronary artery and cerebrovascular diseases respectively. Keywords: Hypertension; Dyslipidemia; Coronary Artery Disease; Cerebrovascular Disorders.